Direito à segurança alimentar e acesso à informação ambiental: agrointoxicação e impactos do consumo de hortifrutigranjeiros - Izolani, Francieli Iung (2021)
This study presents a study about the right to food security and the necessary environmental information for the consumer of non-organic horticultural products in the municipality of Santa Maria and region, starting in 2012, the date of the first Abrasco Dossier on pesticides edition, as a perspective of this right concreteness face the current agrointoxication scenario, analyzing alternatives and investigating limitations. This research aims at solving the following research problem: What are the limits and possibilities for the right to food security accomplishment based on access to environmental information as a condition for reversing an agrointoxication scenario in the consumption of non-organic horticultural products? To solve that question, the methodology follows the quadrennial: Base Theory; Approach; Procedure and Technique. As Base Theory, to justify the option for the systemic-complex approach, authors such as Edgar Morin, Pedro Demo and Fritjof Capra are used; as well Anthony Giddens, Ulrich Beck and Marie Angèle Hermitte to board risk society; Carlos Walter Porto-Gonçalves, Paolo Bifani and Enrique Leff to focus globalization and the sustainability crisis; to understand food security, Renato Sérgio Jamil Maluf e Laíse Graff; for the monocultures panorama and the pesticide usage, Luiz Ernani Bonesso de Araujo, Vandana Shiva and Juliana Santilli; to comprehend Green Revolution and the pesticide impacts, Vandana Shiva and Rachel Carson; to explain the right to information to the consumer of pesticide products, Jerônimo Siqueira Tybusch and Néstor García Canclini; finally, Miguel Altieri and Francisco Roberto Caporal for the agroecology study, and more specifically, for organic production, Elaine de Azevedo and Silvio Roberto Penteado. The approach method is the systemic-complex one, once legal science alone is not able to answer the socioenvironmental matter demands, specially about food security right and its reflexes, connected the need for an interdisciplinary approach and in synergy with different areas. As procedure method, the bibliographic research is used, considering books and papers about this matter, in addition, the documentary analysis, due to the existence of official documents, as well national legislation on pesticides and food security. The techniques are, respectively, abstracts and file elaborations, and figures and graphs elaboration with analyzed data. The obtained results denote the possibility of food security right accomplishment through access to environmental information about the pesticide harms, about the existence of other production alternatives such as agroecology and organic food, about the support network organization between consumer and producer, reversing the current agrointoxication scenario in the consumption of nonorganic horticultural products. The limitations refer to the public policy lack by the corporation-State and the consumer-citizen awakening leading the feeding act to be a political act of counter-hegemonic emancipation.